CHD3 and CHD4 recruitment and chromatin remodeling activity at DNA breaks is promoted by early poly(ADP-ribose)-dependent chromatin relaxation - Smith, Rebecca (Nucleic Acids Res, 2018)
One of the first events to occur upon DNA damage is the local opening of the compact chromatin architecture, facilitating access of repair proteins to DNA lesions. This early relaxation is triggered by poly(ADP-ribosyl)ation by PARP1 in addition to ATP-dependent chromatin remodeling. CHD4 recruits to DNA breaks in a PAR-dependent manner, although it lacks any recognizable PAR-binding domain, and has the ability to relax chromatin structure. However, its role in chromatin relaxation at the site of DNA damage has not been explored. Using a live cell fluorescence three-hybrid assay, we demonstrate that the recruitment of CHD4 to DNA damage, while being poly(ADP-ribosyl)ation-dependent, is not through binding poly(ADP-ribose). Additionally, we show that CHD3 is recruited to DNA breaks in the same manner as CHD4 and that both CHD3 and CHD4 play active roles in chromatin remodeling at DNA breaks. Together, our findings reveal a two-step mechanism for DNA damage induced chromatin relaxation in which PARP1 and the PAR-binding remodeler activities of Alc1/CHD1L induce an initial chromatin relaxation phase that promotes the subsequent recruitment of CHD3 and CHD4 via binding to DNA for further chromatin remodeling at DNA breaks.